Unveiling the consequences of environmental variation and species abundances on beach taphofacies in Bahamas: The role of cementation and exhumation - Bayer, María Sol (2019)
Although environmental variability generates differences in the preservation of shell assemblages, intrinsic variations in shell characteristics can confound the effects of environment on preservation. However, several studies proposed that the composition of shell supply only affects the intensity of alteration but not its preservation trend along the environmental gradient and that environmental variability represents a major driver of taphofacies preservation. Here, we examine whether taphonomic differences among four infaunal and aragonitic bivalve species differing in shell thickness affect the definition of beach taphofacies in tropical carbonate environments on San Salvador Island (Bahamas). We show that (1) taphofacies can be discriminated with respect to (a) wave and storm activity as a function of exposure to Trade Winds, and (b) sandy beaches versus beaches with a mixture of sands and beach rock (representing a source of exhumed and cemented shells), and (2) species-specific bivalve assemblages show similar gradients in preservation, documenting that differences in preservation between species have minor effects on taphonomic discrimination of beach environments. Environments with a mixture of sands and beach rock are characterized by higher frequency of external cementation and abrasion than sandy beaches. Shells from low-energy beaches are more fragmented and discolored than shells from high-energy beaches. Previous studies showed that shells from San Salvador sandy beaches are more time-averaged than shells from rocky beaches. Differences in preservation between these two environments indicate two pathways: (1) assemblages on sandy beaches are degraded at higher rate but are enriched by old exhumed and lithified shells, and (2) assemblages on rocky beaches are cemented at higher rate. Old and lithified shells on sandy beaches are probably derived from submerged or exposed beach rock patches, leading to the mixture of young, well-preserved shells with old, poorly preserved shells. Shells on sandy beaches thus experience a complex history of burial and exhumation before their final deposition. Therefore, shell assemblages in lower energy carbonate environments from San Salvador Island are highly time-averaged, with the presence of old, poorly preserved shells. The depositional environment is thus the dominant factor controlling the structure of San Salvador beach taphofacies.